SEARCHING FOR RESISTANCE SOURCES TO WHEAT COMMON BUNT (Tilletia caries (DC.) - Aigul Madenova,; Kanat Galymbek,; Alma Kokhmetova,; Bakirov S.B.,; Zhenis Keishilov, (Scientific Journal of Pedagogy and Economics, 2021)
Common bunt (Tilletia caries (DC.) the disease occurs in areas where autumn wheat is grown. In our country, most of the zoned wheat varieties are infected with this disease. Therefore, foreign germoplasm should look for sources of strength. In our research in the field of artificial epizootic environment, the Hungarian 21 varieties of soft wheat Tilletia caries (DC.) of the pathogen was made the phytopathological and genetic-selection analysis. The study revealed that 15 wheat varieties are resistant to diseases, of which 8 wheat varieties were highly resistant to diseases (IT-0). They are; Ati, Békés, Berény, Csillag, Futár, Pilis, Szala and Rege. We say 7 varieties that are resistant to common bunt (IT-1), they are Kalász, Mentor, Göncöl, Fény, Garaboly, Szemes and Vitorlás. The indicator of the biomass index (NDVI) was determined at the stages of vegetative development of plants in ears, flowering phase and milky stage. The average value of the biomass index is higher than 0.70, with a high score of 9 varieties that have Ati, Mentor, Hajnal, Göncöl, Tisza, Csillag, Futár, Garaboly and Szala. As a result of the analysis of structural characteristics, the varieties Körös, Mentor, Tisza, Szala, Szemes and Rege showed a high index for all characteristics. As a result, disease-resistant and high-performance varieties can be presented as common bunt resistant specimens in immune selection.